Recent Trends and Challenges in Development of Smart Systems (International Journal of Engineering and Computer Science, 2017)
The term ―Smart Systems‖ is used to explain the meeting of persistent computing and global data networking. The goal of smart systems is to integrate all intelligent devices with networked systems that are self-sensing, self-controlling, and self-optimizing—automatically, without even human intervention. It would not be far-fetched to call such systems ―self-aware.‖ Smart systems incorporate sensing, actuation and control. They can describe and analyze situations by making analytical, adaptive decisions based on the available data and consequently performing smart actions. The smart system frontier includes machines, devices, people, cyber and physical sub systems and information all connected and interacting in a seamless, adaptive manner. These smart systems have shifted the focus from individual technologies to overall system intelligence, which results in fundamental changes in how the goods and services of tomorrow will be shaped, delivered and monetized.